Plataformas de streaming, rupturas tecnológicas e alterações nas dinâmicas das audiências do espaço audiovisual brasileiro (2011-2021) - Cardoso, Jéferson Cristiano (2022)
This thesis analyzes how different streaming platforms, as a phenomenon and technological disruption, affected Brazilian audiovisual audiences, causing public migrations, which, in other times, were affected by other ruptures, such as the emergence of television, the smartphone, the beginning of the internet by fiber optics, the implementation of CDN for the transmission of data by streaming platforms. Therefore, this phenomenon was analyzed in Brazil in three key periods over 10 years, which are 2011 (beginning of Netflix in Brazil), 2015 (the year with the highest number of pay-TV subscribers in the entire history of the country and the beginning of its decline) and 2021 (pandemic and the massive expansion of the number of streaming players and users who use these services). Thus, it was possible to create a picture of all the changes and ruptures of paradigm that occurred over this decade and organize the proposal of a new concept, that of “hyperaudiovisual”. For this, bibliographic and documentary research was carried out, in which data from Ancine and communication vehicles were used, especially Folha de São Paulo, thus enabling specific comparations and sampling, both over time, as well as through different media and devices. As a result, it was noted that the streaming platforms did not affect the audiences of the cinema, but changed the way of distribution of audiovisual, which ceased to be done by physical means, moving to the online business model. In addition, it also directly impacted the pay television audience, which had 25% of its audience migrated to dozens of streaming platforms. The theoretical basis adopted for the research includes authors such as Anderson (2006), Barone (2013), Bauman (2008, 2009, and 2013), Cardoso (2017), Innis (2011), Jenkins (2009), Johnson (2012), Lipovetsky and Serroy (2009 and 2015), McLuhan (1979), Negroponte (1995), Orozco Gómez (2014a, 2014b, 2020), Scolari (2014a, 2014b), among others.